2010
DOI: 10.1292/jvms.10-0031
|View full text |Cite
|
Sign up to set email alerts
|

Fat Depot-Specific Differences in Angiogenic Growth Factor Gene Expression and Its Relation to Adipocyte Size in Cattle

Abstract: ABSTRACT. Adipocytes derived from different anatomical sites vary in the expression of adipocytokines and growth factor genes. Adipogenesis is tightly associated with angiogenesis, although the regional variation of angiogenic growth factor gene expression in adipose tissues remains unclear. In this experiment, we studied the fat depot-specific differences (subcutaneous, intramuscular, intermuscular, renal, and mesenteric) in the expression of angiogenic growth factor mRNA [vascular endothelial growth factor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
1
22
0
Order By: Relevance
“…Our results revealed that highly methylated transcripts in the LDM of both breeds were mainly associated with muscle differentiation and development, suggesting that m 6 A modification is tissue specific and may play an important role in muscle-related functions. Previous studies have indicated that development and lipid metabolism differ in adipocytes from subcutaneous and intramuscular sources (39,40). Although m 6 A reportedly regulates adipogenesis in 3T3-L1 cell lines (25) and porcine subcutaneous adipocytes (24), whether m 6 A affects IMF deposition in a different way remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that highly methylated transcripts in the LDM of both breeds were mainly associated with muscle differentiation and development, suggesting that m 6 A modification is tissue specific and may play an important role in muscle-related functions. Previous studies have indicated that development and lipid metabolism differ in adipocytes from subcutaneous and intramuscular sources (39,40). Although m 6 A reportedly regulates adipogenesis in 3T3-L1 cell lines (25) and porcine subcutaneous adipocytes (24), whether m 6 A affects IMF deposition in a different way remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mature human adipose tissue extract produces numerous angiogenic factors and induces endothelial tube formation [35]. The expression of VEGF positively correlates to the size of adipocytes [36], and is enhanced by IL-6 [37]. Because I3C was observed to reduce IL-6 expression in the WAT in high-fat-diet-induced obese mice [11] and in LPS-stimulated macrophages [38], we hypothesize that I3C (5–50 μM) suppresses adipocyte-induced angiogenesis both by reducing TG accumulation in mature adipocytes leading to reduce the secretion of angiogenic mediators, and by directly inhibiting IL-6 expression in mature adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Adipogenic and adipokine gene expressions were analyzed by real-time PCR as described previously [39,41]. In brief, total RNA was extracted from adipose tissue using the RiboPure kit (Ambion) according to the manufacturer's instructions.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
“…The standard curve of each product followed the calculation of respective gene expressions. The expression levels of adipogenic and adipokine mRNA were normalized by RPLP0 as an internal control [39,41]. The expression in the HV group in each adipose tissue was set to one, and the expression in the control group was expressed as the value relative to that in the HV group.…”
Section: Rna Isolation and Real-time Pcrmentioning
confidence: 99%
See 1 more Smart Citation